Review on uncertainty of the first-flush phenomenon in diffuse pollution control - Mamun, Abdullah Al; Shams, Shahriar, Md. Nuruzzaman (Springer, 2020)
Several defnitions and criteria of the frst-fush are being used to assess and control the nonpoint source (difuse) pollution. The common consensus is that the frst-fush is generally noticed in the small catchments (e.g.<10 ha) of regular shapes. It is also considered that 80% of the pollution load can be captured by capturing 30% of the runof volume, which is assumed to be due to frst-fush of the storm event. However, such phenomenon is uncertain in the considerably large catchments, principally due to the dilution and delay in transport of the pollutant. This paper critically examines the ‘frst-fush’ phenomenon in controlling difuse pollution based on various studies conducted by the researchers. Based on the review, it can be inferred that the frst-fush may be an efective criterion for sizing on-site treatment facilities for small catchments (with similar dimensions of length and width), from where the runof is expected to reach the treatment facility (roughly) at the same time. However, for the large and elongated catchments with an area covering more than 10 ha, a huge volume of storm runof needs to be captured that would make the treatment system large or less efective. As such, for the community and regional facilities; the presence of the frst-fush needs to be confrmed based on the sampling and analysis of data collected from several storm events of diferent durations and intensities. Therefore, the use of the frst-fush phenomenon should not be applied for the design of storm runof treatment facility in large drainage system (say>10 ha) without on-site monitoring being conducted. However, it is also recommended to come up with a simplistic approach of designing the best management practices (BMPs) to capture and treat certain depth of the initial storm runof (e.g. frst 20 mm), which will help reduce the efect of nonpoint source (NPS) pollution.